PERGESERAN MAKNA “BORU NI RAJA” BAGI PEREMPUAN BATAK TOBA (Studi tentang Perempuan Batak Toba di Desa Buatan Besar Kecamatan Siak Kabupaten Siak Provinsi Riau) - Debora Hutagalung; Bedriati Ibrahim; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack : Boru ni Raja is an honor and respect for every Batak woman who started since she was born into the world. The purpose of this paper is 1) to find out the true meaning of